Impact of treatment adherence and inhalation technique on asthma outcomes of pediatric patients: a longitudinal study - Lizano-Barrantes, Catalina; Garin, Olatz; Mayoral, Karina; Dima, Alexandra L.; Pont, Angels; Caballero-Rabasco, María Araceli; Praena-Crespo, Manuel; Valdesoiro-Navarrete, Laura; Guerra, María Teresa; Bercedo-Sanz, Alberto; Ferrer, Montse (Frontiers in Pharmacology, 2024)
We aimed to evaluate the longitudinal relationships, both at between-and withinperson levels, that adherence to inhaled corticosteroids-based maintenance treatment and inhalation technique present with symptom control, exacerbations, and health-related quality of life (HRQoL) in children and adolescents with asthma.Methods: Participants (6-14 years old) from the ARCA (Asthma Research in Children and Adolescents) cohort -a prospective, multicenter, observational study (NCT04480242) -were followed for a period from 6 months to 5 years, via computer-assisted telephone interviews and a smartphone application. The Medication Intake Survey-Asthma (MIS-A) was administered to assess the implementation stage of adherence; and the Inhalation Technique Questionnaire (InTeQ) to assess the five key steps when using an inhaler. Symptoms control was measured with the Asthma Control Questionnaire (ACQ), and HRQL with the EQ-5D and the PROMIS-Pediatric Asthma Impact Scale (PROMIS-PAIS). Multilevel longitudinal mixed models were constructed separately with symptom control, exacerbation occurrence, EQ-5D, and PROMIS-PAIS as dependent variables.Results: Of 360 participants enrolled, 303 (1203 interviews) were included in the symptom control and exacerbation analyses, 265 (732) in the EQ-5D, and 215 (619) in the PROMIS-PAIS. Around 60% of participants were male and most underwent maintenance treatment with inhaled corticosteroids plus long-acting β-agonists in a fixed dose (68-74%). Within-person variability was 83.6% for asthma control, 98.6% for exacerbations, 36.4% for EQ-5D and 49.1% for PROMIS-PAIS. At within-person level, patients with higher adherence had better symptom control (p=0.002) and HRQoL over time (p=0.016). Patients with better inhalation technique reported worse HRQoL simultaneously (p=0.012), but better HRQoL in future assessments (p=0.012). Frequency of reliever use was associated with symptom control (p<0.001), exacerbation occurrence (p<0.001), and HRQoL (p=0.042); and boys were more likely to present better symptom control and HRQoL than girls.Our results confirm longitudinal associations at within-person level of the two indicators of quality use of inhalers: for adherence to maintenance treatment with symptom control and HRQoL, and for inhalation technique with HRQoL. Although treatment adherence showed to be excellent, a third part of participants reported a suboptimal inhalation technique, highlighting the need of actions for improving asthma management of pediatric population.